SAVE: a suicide prevention program for schools - Hertel, Silke; Lintner, Anja; Krein, Ulrike; Rohrbach, Theresa; Bockhoff, Katharina; Bruder, Simone (Journal of Self-Regulation and Regulation, 2020)
Suicide is the second most frequent cause of death among young people aged 15 to 20 years. However, it is unfortunately a taboo topic in today’s society (Federal Statistical Office, 2018). Suicide prevention among adolescents therefore is of high relevance. Schools, as an important learning and living environment for young people, off er a framework for suicide preventi on initiatives such as gatekeeper trainings and psychoeducational programs. Persons involved in school life can act as gatekeepers, perceiving warning signals of suicidal behavior and encouraging students at risk of suicide to seek help (Hamann & Schweigert, 2013). The ain focus of the project “SAVE” is health promotion and health maintenance through the promoti on of self-regulati on strategies. The aim is to effi ciently involve the key players in school life – teachers and students – to achieve the greatest possible effect in terms of suicide prevention. Against this background, gatekeeper trainings and psychoeducati onal preventi on programs are combined and a cooperation with regional care structures is established. This multi -perspecti ve approach, based on an innovati ve combination of these three components, is intended to overcome weaknesses in previous preventive approaches. The program will be evaluated within the scope of an interventi on study at two locations (Darmstadt and Heidelberg). The results will allow conclusions to be drawn about the further development of suicide preventi on approaches and their implementati on in schools. Training materials will be made available to the public at the end of the project.
Gesehen am 19.10.2020